Does Board Diversity Influence Financial Performance? - Tarigan, Josua; Hervindra, Christoforus; Hatane, Saarce Elsye (Universitas Prasetiya Mulya, 2018)
This study extends the empirical evidence on the diversity on board and its impact to the financial performance in Indonesian context. Board diversity, as the independent variable uses three indicator variable of gender diversity, nationality diversity, and education diversity. Aside from traditional proportion measurement, Blau Index also used to measure the heterogeneity degree of each proxy of diversity in this study. This research is focused on the manufacturing companies since manufacturing industry is the largest contributor to the Indonesian GDP. The observation in this research including 525 firm-years from 105 listed manufacturing companies. The result of the study reveals that the heterogeneity in terms of nationality is beneficial for the company as it gives a positive impact to the financial performance measures, while gender and education heterogeneity is proven otherwise.